Kontaminasi Kerang Filter Feeder Perna viridis Linnaeus, 1758 (Bivalvia: Mytilidae) oleh Pestisida Organofosfat di Perairan Laut Brebes Jawa Tengah Indonesia - Chrisna Adhi Suryono; Irwani Irwani; Baskoro Rochaddi; Wilis Ari Setyati; Agus Indardjo (Jurnal Kelautan Tropis, 2021)
In the last five years, organophosphate pesticides has been introduced in red onions fields in Brebes.  This will broadbly impact to the ecosystem, including the filter feeder marine organisms such as green mussel P. viridis. This article presents the occurrence level of organophosphate pesticides residues in marine waters and green mussel which has collected on Brebes marine areas. Some selected organophosphate pesticides compounds (Chlorpyrifos, Profenofos, Diazinon, Fenitrothion, Malation and Methidathion) of contaminant have been determined. The samples were then analyzed by using gas chromatography and followed by using the method of Standard Method Examination. The results showed that average of six residues (Chlorpyrifos, Profenofos, Diazinon, Fenitrothion, and Malation) in marine water were undetected (bd) (<0.0004 ppm). The merely concentration of PPOs detected was Chlorpyrifos 0.31 µg/L detected in green mussel. The concentration of organophosphate pesticides in these areas might contribute by the usage of organophosphate pesticide from red onion fields Dalam lima tahun terakhir, pestisida organofosfat mulai diperkenalkan di ladang bawang merah di Brebes.  Hal ini secara luas akan berdampak pada ekosistem, termasuk organisme laut filter feeder seperti kerang hijau P. viridis.  Artikel ini menyajikan tingkat residu pestisida organofosfat di perairan laut dan kerang hijau yang terkumpul di wilayah perairan Brebes. Beberapa senyawa pestisida organofosfat terpilih (Klorpirifos, Profenofos, Diazinon, Fenitrothion dan Malation) untuk dianilisa.  Sampel kemudian dianalisis dengan menggunakan kromatografi gas dan dilanjutkan dengan metode Pemeriksaan Metode Standar. Hasil penelitian menunjukkan bahwa rata-rata enam residu (Klorpirifos, Profenofos, Diazinon, Fenitrothion, dan Malation) di perairan laut tidak terdeteksi (bd) (<0,0004 ppm). Konsentrasi OPP yang terdeteksi hanyalah Klorpirifos 0,31 µg/L yang terdeteksi pada kerang hijau. Konsentrasi pestisida organofosfat di daerah tersebut kemungkinan besar disebabkan oleh penggunaan pestisida organofosfat dari ladang bawang merah.